An adsorptive approach to enhance the 2-phenylethanol (2-PE) production from L-phenylalanine (L-Phe) biotransformation - Braga, Adelaide (2018)
[Excerpt] Introduction: The consumers demand for flavors produced by natural means has led to a decrease of natural resources and, in this scenario the use of microorganisms as biotechnological platforms for its production is becoming a promising alternative. 2 - PE is an aromatic alcohol with a delicate fragrance of rose petals. In fact, product inhibition during biotransformation limits the final 2 - PE concentrations in conventional biotransformation. In order to improve 2 - PE production a strategy applying in situ product removal by adsorption was investigated. [...]